ANTAGONISM TEST OF PROBIOTICS BACTERIA ISOLATED FROM BLACK TIGER SHRIMP (Penaeus monodon) AGAINST PATHOGENS (Aeromonas hydrophila, Pseudomonas sp and Vibrio alginolyticus) - Nursit Wijayanto; Feliatra '; Syahril Nedi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
AbstractProbiotics is one effective strategy in an effort to cope with the disease by pathogenic bacteria. The study aims to determine the level of pathogenic bacteria were isolated from the candidate probiotic intestinal tiger shrimp against pathogenic bacteria A. hydrophila, Pseudomonas sp and V. alginolyticus. Expected candidate probiotics can be used to combat the disease in fish and shrimp farming. Antagonism using disc diffusion test. Four isolates of candidate probiotic bacteria more dominant round, milky white color and yellow, smooth or scalloped edge. Four candidate probiotic bacteria can inhibit pathogenic bacteria A. hydrophila, Pseudomonas sp and V. alginolyticus. The highest inhibition zone on the candidate probiotics P1 against A. hydrophila, Pseudomonas sp of 11.7 mm and 11.1 mm. The highest inhibition zone on V.alginolyticus the candidate probiotic bacteria P2 of 11.4 mm.Keywords: Probiotics, Tiger Shrimp, antagonists, A. hydrophila, Pseudomonas sp,V. alginolyticus.